Fast-food exposure around schools in urban Adelaide. Issue 17 (14th June 2016) - Coffee, Neil T; Kennedy, Hannah P; Niyonsenga, Theo
Abstract: Objective: To assess whether exposure to fast-food outlets around schools differed depending on socio-economic status (SES). Design: Binary logistic regression was used to investigate the presence and zero-inflated Poisson regression was used for the count (due to the excess of zeroes) of fast food within 1000 m and 15000 m road network buffers around schools. The low and middle SES tertiles were combined due to a lack of significant variation as the 'disadvantaged' group and compared with the high SES tertile as the 'advantaged' group. School SES was expressed using the 2011 Australian Bureau of Statistics, socio-economic indices for areas, index of relative socio-economic disadvantage. Fast-food data included independent takeaway food outlets and major fast-food chains. Setting: Metropolitan Adelaide, South Australia. Subjects: A total of 459 schools were geocoded to the street address and 1000 m and 1500 m road network distance buffers calculated. Results: There was a 1·6 times greater risk of exposure to fast food within 1000 m (OR=1·634; 95 % 1·017, 2·625) and a 9·5 times greater risk of exposure to a fast food within 1500 m (OR=9·524; 95 % CI 3·497, 25·641) around disadvantaged schools compared with advantaged schools. Conclusions: Disadvantaged schools were exposed to more fast food, with more than twice the number of disadvantaged schools exposed to fast food. The higher exposure to fast food near more disadvantaged schools may reflect lower commercial land cost in low-SES areas, potentially creating more financially desirable investments for fast-food developers.